Cloning, expression and bioinformatics analysis of a putative pigeon melanoma differentiation-associated gene 5. Issue 2 (4th March 2019) - Li, G.-Q.; Tian, Y.; Chen, L.; Shen, J.-D.; Tao, Z.-R.; Zeng, T.; Xu, J.; Lu, L.-Z.
ABSTRACT: 1. Melanoma differentiation-associated gene 5 ( MDA5 ) is a critical member of cytosolic pattern recognition receptors (PRRs) that recognise viral RNA and mediate type I interferon secretion in host cells. 2. The objective of the present study was to identify and characterise the structure and expression of pigeon MDA5. 3. The full-length MDA5 cDNA was cloned from pigeon spleen using RT-PCR and RACE. The distribution and expression level of pigeon MDA5 in different tissues were determined by QRT-PCR. 4. The results showed that the full-length pigeon MDA5 cDNA had 3858 nucleotides (containing a 210-bp 5ʹ-UTR, a 3030-bp open reading frame and a 618-bp 3ʹ-UTR) encoding a polypeptide of 1009 amino acids. The deduced amino acid sequence contained six conserved structural domains typical of RIG-I-like receptor (RLR), including two tandem arranged N-terminal caspase activation and recruitment domains (CARDs), a DEAH/DEAD box helicase domain (DExDc), a helicase superfamily c-terminal domain (HELICc), a type III restriction enzyme (ResIII) and a C-terminal regulatory domain (RD). 5. The pigeon MDA5 showed 84.8%, 87.3%, 87.9% and 87.2% amino acid sequence identities with previously described homologues from chicken, duck, goose and Muscovy ducks, respectively, and phylogenetic analysis revealed a close relationship among these MDA5. 6. Pigeon MDA5 transcript was ubiquitously expressed in all seven tissues tested in healthy pigeons and showed a high level in the thymus gland and kidney. 7. These findings lay the foundation for further research on the function and mechanism of MDA5 in innate immune responses related to vaccinations and infectious diseases in the pigeon.